Маgijata na slovoto i mylčanieto v obreda – formuli i funkcii - Kolarska, Irina (Wydawnictwo Naukowe UAM, 2012)
Beliefs and perceptions of word are based on existing mythological layer of culture that has specific mechanisms and functions. This mythological context of word determines its acceptance as a magical tool that has a certain force of impact. The power of speech is invisible, but exactly by the word, the individual and the community identify themselves and provide a link between past, present and future. One of the most significant events of word (or speech) is connected with its use in ritual. The reason of this is that the importance is attached to the ritual and to the consequences of its performing. Ritual word has an impact on society, and nature and the individual by verbal formulas that contribute to its realization. Depending on the ritual, word can both perform different functions and act as a specific magical tool.
The Magic of Word and Silence in the Ritual – Formulas and Functions
Keywords: ritual word; magic; verbal formulas; functions; monological and dialogical forms of ritual words; silence